Glycine protects partial liver grafts from Kupffer cell-dependent ischemia-reperfusion injury without negative effect on regeneration - Saeedi, Mohammed al; Schultze, Daniel; Nickkholgh, Arash; Herr, Ingrid; Zorn, Markus (Amino acids, 2019)
Donor preconditioning with glycine prevents Kupffer cell-dependent reperfusion injury to liver grafts. Partial liver grafts need to regenerate and grow in size after transplantation; however, glycine inactivates Kupffer cells, which are important for hepatic regeneration. Thus, this study was designed to evaluate the impact of donor preconditioning with glycine after partial liver transplantation (pLTx). PLTx was performed in 28 female Sprague-Dawley rats. Glycine (1.5 ml, 300 mM; i.v.) was given to 14 live donors before organ procurement. Liver enzymes and histology were investigated 8 h after reperfusion to index liver injury and leukocyte infiltration. Hepatic microperfusion and leukocyte-endothelium interaction were assessed using the in vivo fluorescence microscopy method. Ki-67 and TNF-α were detected by immunohistochemistry for regeneration and Kupffer cell activation. Glycine significantly increased survival from 0% in controls to 40%, while both liver enzyme levels and necrosis were decreased to about 50% of controls (p < 0.05). Sinusoidal blood flow increased by 40-80%, while leukocyte-endothelium interaction decreased to 30% of control values (p < 0.05). While Kupffer cell-derived TNF-α decreased to 70% of controls, there was no difference between groups in Ki-67 expression. Data presented here clearly demonstrate that glycine protects partial liver grafts from reperfusion injury without effects on regeneration.
Gesehen am 27.06.2019